The Minimum Wage, Self-Employment, and the Online Gig Economy - Glasner, Benjamin (Journal of Labor Economics, 2023)
This paper estimates the effect of minimum wage increases on work that is not covered by minimum wage laws. I find that minimum wage increases in the early 2000s resulted in small reductions in engagement in traditional self-employment. Following the development of the online gig economy in the 2010s, a 10% increase in the minimum wage increased the number of nonemployer establishments classified as transportation and warehousing services by approximately 2.7%. The counties most likely to exhibit a positive relationship between the minimum wage and participation in uncovered work are those with low labor market concentration and active Uber marketplaces.